How important are training management quality and environmental conditions in influencing the effectiveness of tourism training? - Ingkadijaya, Rahmat; Desafitri RB, Linda; Djati, Sundring Pantja; Akbar, Mohammad Moudika (Technium Social Sciences Journal, 2021)
The implementation of training should be managed properly so that the objectives or benefits of the training can be achieved effectively. The purpose of this study was to analyze (1) the effect of training management quality on training effectiveness, (2) the influence of environmental conditions on training effectiveness, and (3) the effect of training management quality and environmental conditions simultaneously on training effectiveness. This study used a survey method. Data collection was carried out through distributing questionnaires directly to participants who had attended training at a training center for educators and educational personnel in business and tourism owned by the Indonesian government from 2017 to 2019, totaling 100 people who were selected by purposive sampling. The data analysis used is descriptive analysis and multiple linear regression analysis. The results of this study indicate that the quality of training management has a significant effect on the effectiveness of training, environmental conditions have a significant effect on the effectiveness of training, and the quality of training management and environmental conditions simultaneously have a significant effect on the effectiveness of training.